Compelling trustees to exercise their discretion: A principle of non-intervention? - TANG, Hang Wu (Institutional Knowledge at Singapore Management University, 2018)
This article explores the limitsof the principle of non-interference and examine situations where the courtshave overridden the discretion of the trustee and compelled the trustee to actin a particular manner. While there havebeen numerous instances where the courts have avoided the trustee’s act, thecases where the courts have actually compelled a trustee to exercise a power ina particular manner are relatively few. The thesis of this article is that amore helpful way to conceptualise the philosophy behind the judicial control ofa trustee’s discretion is not to say that the court is bound by a so-calledprinciple of non-interference; rather, the contention made here is that it ismore accurate to say that the courts will interfere if the trustee has abusedhis or her discretion. The advantage of statingthe rule in a positive form is that it makes it clear that the trustee’sdiscretion is not uncontrolled and the courts may interfere with the exerciseof the discretion in appropriate cases.